Meletakan Kedudukan PAK Secara Tepat dan Tepat Sasaran Seperti Ajaran Yesus - Hamambira, Domianus Lodu (Sekolah Tinggi Teologi Jaffray Jakarta, 2019)
Put a Christian Religion Education precisely and right on target as the teachings of Jesus for the sake of faith progress. The principle is build on Biblical and historical fact that Jesus is the coaches are taught good news and therefore his disciples called Him Teacher (John 3:2; Mat. 7:29). Understanding of the Christian Religion Education deeply as taught by Lord Jesus at least bring advantage, which are; growth of faith for individual, build a willingnes to be more initiative, proactive, and innovative in taught of Christianity optimaly, and also bring impact for many people to grow in faith. However, in many class discussion, seminars, and observation both directly and indirectly contain of opinions explain that the role of Christian Religion Education is not yet appropriate to the target and churchess do not equal in applying Christian Religion Education enterestingly and being maximum. Therefore, very important to understand the role of Christian Religion Education which contain of important staples, in from of special values, purposes, history, philosophy, basic biblical theological in order to implement Christian Religion Education in more advance and right on target. Christianity education can be said diferent from education in general since Christian Education was programmed or planned by GOD Himself and bequeathed to those who has been chosen individualy or in community to forward Jesus taught, testify, taugth and preaching the good news from age to age. Called that education Christianity different from education in general are Christianity education can be understood as religious education, spiritual education or education of the faith. To equip believers with knowledge and truth trough the holy spirit works.